An Evaluation of English Language Learning Based on Outcome-Based Education (OBE) in Higher Education - Agustin Nurya Savitri; Darry Christine Silowaty Purba (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The implementation of Outcome-Based Education (OBE) in Indonesian higher education has reshaped English language learning, yet systematic evaluation of its effectiveness remains limited. This research addresses the urgent need to evaluate whether OBE-based English instruction achieves intended learning outcomes, given persistent gaps between curriculum design and classroom practice. The objective of this study is to evaluate OBE-based English language learning in higher education, specifically examining outcome achievement, curriculum-practice alignment, implementation challenges, and stakeholder perception consistency. A qualitative evaluative approach was employed, involving semi-structured interviews with six English instructors, focus group discussions with fifteen students across proficiency levels, classroom observations of twenty sessions, and document analysis of course syllabi and OBE policy documents. Thematic analysis revealed four main findings: OBE learning outcomes are partially achieved, with writing outcomes significantly lower than speaking and listening; substantial misalignment exists between OBE curriculum documents and practice, with teacher-centered instruction dominating 70% of observed sessions; multidimensional challenges including resource limitations, pedagogical difficulties, and cultural factors constrain implementation; and instructors systematically overestimate student outcome attainment compared to student self-assessments. The study concludes that OBE-based English learning requires targeted writing interventions, instructor professional development in authentic assessment design, technology infrastructure investment, multi-stakeholder evaluation mechanisms, and cultural adaptation strategies. Further longitudinal and comparative studies across institutions are recommended.